A Critical Analysis of Five Eyes Alliance in the Indo-Pacific Region (Journal of Social Sciences Review, 2025)
The Indo-pacific region has become a hub of geopolitical competition among regional and extra regional powers. The Five Eyes alliance being composed of the US, the UK, Australia, Canada and New Zealand has grown its potential activities to keep check on geopolitical adversaries in the Indo-Pacific region particularly China. This study is conducted to examine the potential of the alliance addressing geopolitical threats and its effectiveness to counter the Chinese geopolitical expansion in the Indo-Pacific region. Utilizing a qualitative interpretivist approach this endeavour evaluate the cooperation among the member states within the context of the regional dynamics. By analysing primary and secondary data this study disclose that the Five Eyes alliance play pivotal role in regional security collaboration. But it faces certain limitations in countering Chinese expansion in the Indo-Pacific region in the dynamic nature of international geopolitics. The findings indicates that the alliance is influential but its potency to effectively restraint Chinese expansion is limited.
Keywords: Five Eyes Alliance; Indo-Pacific; The US; China; Geopolitics; Regional Security; Intelligence; Strategy